Hypobaric Unilateral Spinal Anesthesia Versus General Anesthesia for Hip Fracture Surgery in the Elderly: A Randomized Controlled Trial. (22nd September 2022) - Simonin, Marine; Delsuc, Claire; Meuret, Pascal; Caruso, Liana; Deleat-Besson, Robert; Lamblin, Antoine; Huriaux, Laetitia; Abraham, Paul; Bidon, Cyril; Giai, Joris; Riche, Benjamin; Rimmelé, Thomas
Abstract : BACKGROUND: Hypotension during surgery is frequent in the elderly population and is associated with acute kidney and myocardial injury, which are, themselves, associated with increased 30-day mortality. The present study compared the hemodynamic effects of hypobaric unilateral spinal anesthesia (HUSA) to general anesthesia (GA) in patients ≥70 years of age undergoing hip fracture surgery. METHODS: We conducted a single-center, prospective, randomized study. In the HUSA group, patients were positioned with the operated hip above, and the hypobaric anesthetic solution was composed of 9 mg ropivacaine, 5 µg sufentanil, and 1 mL of sterile water. Anesthesia was adjusted for the GA group. Mean arterial pressure (MAP) was measured with a noninvasive blood pressure upper arm cuff every 3 minutes. Hypotension was treated with a bolus of ephedrine and then a continuous intravenous of norepinephrine to obtain a MAP ≥65 mm Hg. Primary outcome was the occurrence of severe hypotension, defined as a MAP <65 mm Hg for >12 consecutive minutes. RESULTS: A total of 154 patients were included. Severe hypotension was more frequent in the GA group compared to the HUSA group (odds ratio, 5.6; 95% confidence interval, 2.7–11.7; P < .001). There was no significant difference regarding the short-term outcomes between the HUSA and GA groups: acute kidney injury (respectively, 5.1% vs 11.3%; P = .22), myocardial injury (18.0% vs 14.0%; P = .63), and 30-day mortality (2.4% vs 4.7%; P = .65). CONCLUSIONS: HUSA leads to fewer episodes of severe intraoperative hypotension compared to GA in an elderly population undergoing hip fracture surgery.